2022
DOI: 10.1101/2022.05.10.491380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures reveal a key mechanism of WAVE Regulatory Complex activation by Rac1 GTPase

Abstract: Rho-family GTPase Rac1 activates the WAVE regulatory complex (WRC) to drive Arp2/3-mediated actin polymerization in many essential processes. Rac1 binds to WRC at two distinct sites—the A and D sites. Precisely how Rac1 binds and how the binding triggers WRC activation remain unknown. Here we report WRC structures by itself, and when bound to single or double Rac1 molecules, at ∼3 Å resolutions by cryogenic-electron microscopy. The structures reveal that Rac1 binds to the two sites by distinct mechanisms, and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…We found that in the absence of Rac1, the Arf1-WRC interaction was weak, with a dissociate constant K D ∼23 µM ( Figure 1C , black). By contrast, in the presence of 100 µM Rac1, which should saturate both A and D sites of the WRC (Chen et al, 2017; Ding et al, 2022), Arf1 binding affinity was increased nearly 30 fold (K D ∼ 0.66 µM, Figure 1C , orange). The enhanced binding was not an artifact of high concentration of free Rac1 included in the assay, as a mutant Rac1, in which the entire Switch I motif critical for WRC binding was removed (herein referred to as Rac1 Dead ; Figure S1A ), could not promote Arf1 binding at the same concentration ( Figure 1C , blue).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…We found that in the absence of Rac1, the Arf1-WRC interaction was weak, with a dissociate constant K D ∼23 µM ( Figure 1C , black). By contrast, in the presence of 100 µM Rac1, which should saturate both A and D sites of the WRC (Chen et al, 2017; Ding et al, 2022), Arf1 binding affinity was increased nearly 30 fold (K D ∼ 0.66 µM, Figure 1C , orange). The enhanced binding was not an artifact of high concentration of free Rac1 included in the assay, as a mutant Rac1, in which the entire Switch I motif critical for WRC binding was removed (herein referred to as Rac1 Dead ; Figure S1A ), could not promote Arf1 binding at the same concentration ( Figure 1C , blue).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, we asked which Rac1 binding event was key to promoting Arf1 binding. To answer this question, we first used single amino acid mutations to specifically disrupt the A or D site from binding to Rac1 (Chen et al, 2017, 2010; Ding et al, 2022) ( Figure 2A , cartoon). When Rac1 binding to the A site was disrupted by Sra1 C179R , Rac1 binding to the D site still enhanced Arf1 binding, but to a lower extent than the WT WRC ( Figure 2A , lane 6, 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations